(untitled) (Journal of Comparative & International Higher Education, 2022)
In this paper, I explore the enactment of institutional autonomy policy as a reform strategy to support the internationalization of higher education in Vietnam. The autonomy policy signifies the transfer of decision-making authority from the ministries to public universities so that university leaders can decide on matters of teaching, research, finance, personnel, and international cooperation. I draw on neo-institutionalism to gain insights on the enactment of autonomy policy and use thematic analysis to analyze data which include policy documents and interviews with senior leaders at one Vietnamese university. The findings indicate that while the autonomy policy has facilitated internationalization agendas with significant outcomes for teaching and research, the policy has been enacted through the interactions of Vietnam’s political features and foreign values. The paper contributes to the understanding of higher education reform in centralized contexts of Vietnam and other post-Soviet countries in response to influences of the globalized knowledge economy.